"On the Cusp": Liminality and Adolescence in Arthur Slade’s Dust, Bill Richardson’s After Hamelin, and Kit Pearson’s Awake and Dreaming - Wills, Deborah; Bright, Amy (Studies in Canadian Literature, 2011)
North American social, cultural, and developmental narratives frequently suggest that the successful conclusion of adolescence lies primarily in moving through and past it. Adolescence is thus represented as both transitional and transitory, a briefly liminal state meant to be resolved by a conclusive departure. However, recent Canadian young adult novels such as Arthur Slade’s Dust (2001), Bill Richardson’s After Hamelin (2000), and Kit Pearson’s Awake and Dreaming (1996) challenge these assumptions by depicting adolescent protagonists who find their identity and their greatest strength in their liminality. The successful adolescents in these novels possess what we might call a transliminal consciousness, a state of mind that allows them to move deftly between the ontologically contradictory states of fantasy and reality. They use the creative and generative potential of dream-space to either create a coherent family or preserve a fragmented family.